1997
DOI: 10.1088/0022-3727/30/2/007
|View full text |Cite
|
Sign up to set email alerts
|

The polishing of diamond

Abstract: Experiments on the analysis of the wear debris produced during the polishing of diamond and the rapid sliding of diamond upon diamond using a high-speed sliding machine are presented. The debris was studied by electron energy loss spectroscopy (EELS) in a scanning transmission electron microscope (STEM) and by transmission electron microscopy (TEM). The aim of the work was to improve understanding of the polishing process. It was found that the debris produced when polishing diamond in a direction on a plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 10 publications
2
40
0
Order By: Relevance
“…A terminology used in the polishing industry and scientific literature refers to the direction of the highest polishing wear rate (in the case of our IIa diamond samples the 100 direction on the {100} crystal plane), as the "easy direction" and the direction with the lowest polishing wear rate (in our samples the 110 or 111 direction in the {100} crystal plane) the "hard direction" . Work by Grillo and Field [17] showed that when polishing {100} diamonds in the 110 direction, or the "hard direction", the polishing debris consists of fragments of diamonds, suggesting the material is being removed by mechanically chipping the surface. This is clearly seen in Fig.1(a) where large chips, several microns in size, are seen on the diamond surface.…”
mentioning
confidence: 99%
“…A terminology used in the polishing industry and scientific literature refers to the direction of the highest polishing wear rate (in the case of our IIa diamond samples the 100 direction on the {100} crystal plane), as the "easy direction" and the direction with the lowest polishing wear rate (in our samples the 110 or 111 direction in the {100} crystal plane) the "hard direction" . Work by Grillo and Field [17] showed that when polishing {100} diamonds in the 110 direction, or the "hard direction", the polishing debris consists of fragments of diamonds, suggesting the material is being removed by mechanically chipping the surface. This is clearly seen in Fig.1(a) where large chips, several microns in size, are seen on the diamond surface.…”
mentioning
confidence: 99%
“…Studies of the polishing residue show both similarities and differences between the directions. Electron energy loss spectroscopy [6] and transmission electron microscopy [7] studies of the polishing residue indicate that it consists mainly of amorphous clusters, although nanometer scale regions with a structure similar to graphite are also observed. When polishing in the hard direction, additional small diamonds (∼1 nm 3 ) are occasionally observed in the residue, although it is unclear whether these originated in the polishing diamond or the polished diamond, and there are also fewer graphitic regions.…”
mentioning
confidence: 99%
“…Furthermore the size of clusters in the residue, and the small amount of material removed per traversal in sliding indenter experiments [4], suggest a mechanism in which only a few carbon atoms are removed in each tribological event. In other respects the hard and soft polishing directions are more similar, for example, the increase in polishing rate in hydrogen and oxygen rich environments [5] and the weak temperature dependence of the rate [6]. Studies of the polishing residue show both similarities and differences between the directions.…”
mentioning
confidence: 99%
“…Perhaps as a result of this, research on diamond wear has tended to branch into two main areas: low speed frictional sliding experiments -measuring friction with controlled contact and atmospheric conditions [5][6][7][8][9][10][11][12][13] and post-wear analysis which has included studies of the diamond surfaces after polishing and friction experiments [14][15][16][17] and debris analysis [9,11,12,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%